(untitled) (Journal of Partial Differential Equations, 2014)
In this paper, we study the boundary-value problem for mixed type equation with singular coefficient. We prove the unique solvability of the mentioned problem with the help of the extremumprinciple. The proof of the existence is based on the theory of singular integral equations, Wiener-Hopf equations and Fredholm integral equations.